Literature Review on the Effectiveness of Mass Drug Administration as a Control of Soil-Transmitted Helminth Infections - Miratul Hasanah; Hamidah Retno Wardani (Jurnal Ilmu-Ilmu Kesehatan, 2026)
Background: Soil-transmitted helminth (STH) infections remain a major public health problem in tropical and subtropical regions, particularly among school-aged children. However, evidence on the long-term effectiveness of Mass Drug Administration (MDA) as a primary control strategy remains inconsistent as a standalone intervention. This study aimed to review the effectiveness of MDA in controlling STH infections and to identify complementary measures required for sustainable control. Methods: A literature review was conducted using PubMed and ScienceDirect databases for articles published between 2015 and 2025. Original research articles focusing on school-aged children were screened based on predefined inclusion criteria. Results: The findings showed that repeated rounds of MDA were associated with reductions in STH prevalence and intensity in some settings. Persistent transmission remained evident with prevalence ranging from around 13% to over 80% despite long-term MDA implementation. Continued infection was consistently associated with poor water, sanitation, and hygiene (WASH) conditions, inadequate hand hygiene practices, and exposure to contaminated water sources. Conclusion: Sustainable control of STH infections requires integrated interventions that combine MDA with improvements in WASH infrastructure, hygiene promotion, and community-based health education to prevent rapid reinfection and achieve long-term public health impact.